Short communication: Sodium chloride levels in pacu (Piaractus mesopotamicus) fingerling feeds free of fish meal - Aguiar, Natalia C.; Zadinelo, Izabel V.; Dias, Patrícia S.; Mauerwerk, Marlise T.; Bombardelli, Robie A.; Meurer, Fábio (Spanish Journal of Agricultural Research, 2022)
Aim of study: To evaluate the effects of increasing NaCl levels on the zootechnical performance of pacu fingerling.Area of study: The experiments were conducted at the Aquatic Organism Production and Reproduction Systems Laboratory belonging to the Federal University of Paraná (UFPR), in the Palotina Sector, Paraná Estate, Brazil.Material and methods: Seven hundred and fifty fingerlings with an average weight of 3.41 ± 0.09 g were distributed in circular boxes, in a completely randomized design consisting of six treatments and five replications. Treatments comprised soybean- and maize-based diets containing increasing levels of NaCl (0.00, 0.25, 0.50, 0.75, 1.00 and 1.25%). The experiments were conducted for 50 days. At the end of the experimental period the fish were fasted for 24 hours, anesthetized, weighed and measured to calculate zootechnical performances. Performance data were subjected to an analysis of variance followed by Tukey’s test when significant differences were found between the means (p<0.05).Main results: The influence (p<0.05) of dietary NaCl levels on final weight, feed intake, apparent feed conversion, specific growth rate, average weight gain, clean trunk production, head carcass yield, headless carcass yield, feed intake and survival was assessed. The results indicate that non-salt treated fingerlings along with the 0.25% salt inclusion treatment led to better feed use, as evidenced by apparent feed conversions of 1.64 and 2.02, respectively.Research highlights: The inclusion of NaCl in pacu fingerling soybean and maize-based diets is not recommended.